(untitled) (Research, Society and Development, 2021)
The consumption of fiberis extrmely important, as its ingestion helps prevent diseases and regulate bowel function, so there is great interest ftom the food industry in the development of new products based on dietary fiber. The objetive of the present work was to elaborate and evaluate the acceptance of cookies made from apple flour. The study was carried out at the Biosaúde laboratory of the Don Bosco Catholic University, in Campo Grande – MS. The flour was prepared from apples from the same batch, dehydrated and crushed. In the cookies formulation, 45% of apple flour was used,which made up its base. The evaluation of the components and their quantity were carried out through chemical analysis, obtaining means and standard deviation. The sensory evaluation had 30 untrained judges, in which two tests were used during the research: the hedonic scale and the attitude or purchase intention scale. The results obtained presented an innovative cookies with apple flour, this one had a great response of acceptability index (85,08%), standing out in the purchase intentions. Through the data obtained, it is concluded that the product obtained can be commercially included under the sensory point of view, in addition to presenting an excellent nutritional profile, aiming at the treatment and prevention of diseases such as diabetes, dyslipidemia and intestinal disorders.